Abuse Liability Assessment of the RELX Infinity® Electronic Nicotine Delivery System Among Adult Smokers and Electronic Nicotine Delivery System Users - Graff Donald W.; Fearon Ian M.; McClean Mark; Melara Rebeca; Vemuri Ramadevi; Mills Catherine (Contributions to Tobacco and Nicotine Research)
Nicotine pharmacokinetics and subjective effects are important factors in assessing the abuse liability of tobacco products such as electronic nicotine delivery systems (ENDS). In addition, an abuse liability determination is informative in assessing the ability of ENDS to support switching from cigarette smoking.